Covid-19 Em Gestantes E Recém-Nascidos: Situação Epidemiológica Do Espírito Santo - Santos, Ana Paula Brioschi Dos (2024)
Introduction: The Coronavirus disease (COVID-19), caused by SARS-CoV2, was declared a pandemic by the World Health Organization (WHO) in 2020. Pregnancy was not initially considered a risk group, however, it was noticed that when infected, pregnant women were more likely to present a more severe clinical picture and death compared to non-pregnant reproductive-aged women, especially among low- and middle-income countries. Objective: To analyze the effects of COVID-19 on maternal and infant outcomes and the quality of data from 2020 to 2022 in Espírito Santo. Methodology: To achieve the objectives, three stages were carried out in the study. The first stage was a descriptive study using data obtained from e-SUS VS. Completeness in filling out the notification was classified as excellent (less than 5% incomplete filling), good (5% to 10%), fair (10% to 20%), poor (20% to 50%), or very poor (50% or more). The timeliness was defined by the difference between the dates of symptom onset and notification. The second stage was a retrospective cohort study among pregnant women with secondary data from the National Live Birth Information System (SINASC), the National Mortality Information System (SIM), and the e-SUS Surveillance Health System. Pregnant women confirmed for COVID-19 had a positive RT-PCR between March 2020 and May 2021, while pregnant women without COVID-19 were those without notification for the disease. Maternal death, fetal death, and stillbirth were evaluated as primary outcomes. In the third stage, a case-control study was conducted from a historical cohort of pregnant women confirmed for COVID-19 in the state of Espírito Santo between 2020 and March 2022. Cases were selected from maternal deaths confirmed by COVID-19 registered in e-SUS VS and SIM, and controls were selected from the cohort of pregnant women confirmed for COVID-19 who were cured of the disease. Results: In the first stage of the study, 8,989 notifications in pregnant women were identified. The notification for COVID-19 in e-SUS VS has 59 variables, the completeness of 53 (89.83%) variables was excellent, good, or fair in 1 (1.70%), and poor in 4 (6.77%). The timeliness had an average of 3.37 days. In the second stage, 68,673 pregnant women not notified as suspected of COVID-19 and 1,386 with a confirmed diagnosis of COVID-19 were included. Among pregnant women with COVID-19, 1,013 (73.0%) were aged 20 to 34 years, 655 (47.2%) were of mixed race, 907 (65.4%) had ≥ 8 years of schooling, in the third trimester of pregnancy (41.5%), undergoing cesarean section (64.5%). In adjusted analyzes, COVID-19 in pregnancy presented a higher risk of maternal death (relative risk [RR] 18.73 - 95% confidence interval [CI95%] 11.07-31.69), fetal death/stillbirth (RR 1.96 - CI95% 1.18 -3.25), premature birth [RR 1.18-CI95% 1.01-1.39], cesarean section (RR 1.07 - CI95% 1.02-1.11), and cesarean section before the onset of labor (RR 1.33 - CI95% 1.23-1.44). In the third stage, the sample consisted of 2,300 pregnant women, the matching of cases and controls was performed, and 37 cases and 111 controls were selected. Among the pregnant women who died, 35 (67.57%) were non-white, 26 (70.27%) had ≥ 8 years of study. 27 (72.97%) were infected in the 3rd gestational trimester, 24 (77.42%) had up to 6 prenatal consultations, and 15 (48.39%) had 3 or more previous pregnancies. Regarding the vaccination status among the deaths, 3 (8.11%) were vaccinated during pregnancy, and 36 (97.30%) had a record of COVID19 infection before the first vaccine dose, 40.54% had adynamia, and 13 (35.14%) of the pregnant women who died presented at least 1 comorbidity. In the adjusted model, the highest chance of maternal death was described among pregnant women infected in the third gestational trimester (OR 4.67 - CI95% 1.51-14.46), with adynamia (OR 4.33 - CI95% 1.41- 13.31) with at least one comorbidity in pregnancy (OR 3.82 - CI95% 1.16-12.55). Having more than 7 prenatal consultations remained with the lowest chance of progressing to death (OR 0.91 - CI95% 0.31-0.26). Conclusion: The quality of data regarding pregnant women registered in e-SUS VS was excellent. COVID-19 can contribute to unfavorable outcomes in pregnancy. The results showed that pregnant women infected with SARS-CoV-2 had a higher risk of maternal death, fetal death/stillbirth, premature birth, cesarean section, and cesarean section before the onset of labor. Factors related to prenatal care, exposure to the virus in the third trimester of pregnancy, as well as factors related to pre-existing diseases and conditions in pregnant women infected with SARS-CoV-2, increase the chance of maternal death.